PENGARUH STRATEGI KOMUNIKASI PEMASARAN TERPADU TERHADAP KUNJUNGAN WISATAWAN DOMENSTIK PADA EKOWISATA TAMAN NASIONAL BALURAN DI KABUPATEN SITUBONDO - Ediyanto Ediyanto (CERMIN: Jurnal Penelitian, 2018)
This Research aims to describe the effect of an integrated marketing communication strategy consisting of variables of Direct Marketing, Sales Promotion, Public Relations, Personal Sales, and Advertising as Independent variables (X) of Domestic tourist interest as dependent variable (Y). This Research used primary data in the form of questionnaires distributed to 100 respondents using probability sampling technique with equation model Multiple Linear Regression Analysis SPSS 22.0. The results showed that Fcount was 41,672> Ftable of 2,368, so simultaneously variables of direct marketing, sales promotion, public relations, personal sales, and advertising proved to have a positive and significant effect on domestic tourist interest. Regression coefficients for direct marketing are 0.181, sales promotions 0.155, public relations 0.182, personal sales 0.148 and advertising 0.249, with a significance level of 95%, of all factors have a positive influence on the interest of domestic tourists to visit Baluran national park tourist sites, but the dominant influence is the advertising factor. The result of coefficient of determination doubled by 0,673, this mean 67,3% variation of change of tourist interest can be explained by direct marketing variable, sales promotion, public relation, personal selling, and advertisement while the rest equal to 32,7% caused by other factor.